Analisis Variasi Kecepatan Potong Dan Kedalaman Potong Terhadap Nilai Kekasaran Permukaan Dan Getaran Pada Pembubutan Silindris Material Baja ST 60 (Department of Mechanical Engineering, Faculty of Engineering, Universitas Negeri Semarang, 2021)
Conventional lathes are still often used, but the problem is that conventional lathes are difficult to get really good product quality (geometric dimensions, surface roughness and appropriate reflective geometries) due to human factors, the cutting parameters used and the condition of the machine itself. The purpose of this study was to determine how much the effect of cutting speed and depth of cut on vibration and surface roughness in the cylindrical turning process. This research is a quantitative research using experimental methods. For data collection using the technique of observation and documentation methods. Date analysis techniques using regression analysis techniques. The research results that have been obtained, it is known that the highest engine vibration value is 5.4 m/s2 and the lowest is 1.8 m/s2. The highest vibration value of the chisel is 5 m s2 and the lowest is 1 m/s2. And for the highest surface roughness is 5.0 µm and the lowest is 2.33 µm. And it can be concluded that the higher the cutting speed and the depth of cut, the machine vibration, chisel vibration and roughness will be higher.